SAT0293 Comparison of european score and two national guidelines calibrated for cardiovascular risk assessment in patients with psoriatic arthritis. (23rd January 2014) - Magro-Checa, C.; Rosales-Alexander, J.L.; Salvatierra, J.; Cantero-Hinojosa, J.; González-Domínguez, J.; Raya-Άlvarez, E.
Abstract : Background: Stratifying cardiovascular risk using risk charts is central to decision-making on treatment to prevent cardiovascular disease. EULAR task force on cardiovascular (CV) risk management in patients (pts) with inflammatory arthritis recommends the use of the SCORE chart when no local guidelines are available. In our country, two charts have been calibrated and are widely used to calculate CV mortality at 10 years, the SCORE table (cSCORE) and the Framingham-Wilson (REGICOR). Objectives: To assess the CV risk in Psoriatic Arthritis (PsA) pts using the SCORE for low risk European countries (eSCORE) and compare it with the cSCORE and the REGICOR. Furthermore, we analyzed the correlation of several clinical and serological variables with these indexes and the percentage of pts that received adequate therapy for the management of CV risk. Methods: This cross-sectional study included 147 consecutive pts who fulfilled the CASPAR criteria followed in our outpatient clinics. Patients with a previous CV event and diabetics were excluded. The following data were recorded for analysis: sex, age, body mass index, classic CV risk factors, lipid profile, duration in years since diagnosis, clinical patterns of the PsA, treatment, and inflammatory markers. The eSCORE function model, the cSCORE and the REGICOR were compared and the concordance (Kappa Index) between the three guides calculated. According to our national guidelines, a high CV risk has been defined by a SCORE ≥5% and REGICOR ≥10%, the cutoff point recommended to start treatment. Results: The mean eSCORE was 1, 36±2, 25% and 18 pts (11, 4%) were above the threshold of high or very high CV risk (≥5%). After applying the cSCORE the values were 2, 23±3, 48% and with REGICOR were 4±3, 4%. Therefore, 34 pts (21, 5%) and 20 pts (12, 7%) were reclassified as high o very high CV risk (SCORE ≥5%, REGICOR ≥10%) respectively. Multivariate regression analysis showed that the most important prognostic factor for predicting the cSCORE was the age (Total R-square 64%; p=0, 000) followed by systolic blood pressure. Of notice, the ESR was also a prognostic factor of the SCORE (p<0, 05). Both eSCORE and REGICOR showed a bad concordance (Kappa Index 0, 63 and 0, 55 respectively) with cSCORE. Based on the eSCORE, the percentage of high and very high CV risk pts treated with antihypertensive and lipid-lowering treatment was 75% and 85% of pts respectively, but when pts were reclassified with cSCORE, this percentage decreases to 65, 21% and 35, 29%, and with REGICOR to 55, 55% and 22, 22% respectively. Conclusions: Assessment of the CV risk in PsA pts applying the eSCORE or REGICOR leads to an underestimation of the risk in comparison with the application of the cSCORE, which have an impact on the correct management of these pts. Variable analysis showed that ESR, but not CRP, was a prognostic factor of the SCORE what suggests that sustained inflammation could play a role in the increase of CV risk. References: Peters MJL et al. EULAR evidence-based recommendations for cardiovascular risk management in patients with rheumatoid arthritis and other forms of inflammatory arthritis. Ann Rheum Dis. 2010;69:325–331. Disclosure of Interest: None Declared